Deaf utopia : a memoir-- and a love letter to a way of life - DiMarco, Nyle, 1989-; Siebert, Robert (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2022)
Before becoming the actor, producer, advocate, and model that people know today, Nyle DiMarco was half of a pair of Deaf twins born to a multi-generational Deaf family in Queens, New York. Nyle shares stories, both heartbreaking and humorous, of what it means to navigate a world built for hearing people. This is more than a memoir, it is a cultural anthem - a proud and defiant song of Deaf culture and a love letter to American Sign Language, Nyle's primary language.
How I failed my first test the day after I was born -- Queens, New York -- Fire in the belly -- Roadside arts and crafts -- Wanderings -- Them hearing, me deaf -- Storms -- The kitchen light -- Fighting back -- Guatemala -- Explorations -- Use your voice -- I'm sold -- War heroes -- Tears of joy -- Fluid -- Boombox -- Silence, deaf history, and the last dance -- Embracing me -- Home movies.
Includes bibliographical references (pages 309-313).
Keywords: DiMarco, Nyle, -- 1989-.; Acteurs -- États-Unis -- Biographies; Actors -- United States -- Biography; BIOGRAPHY & AUTOBIOGRAPHY / LGBT; BIOGRAPHY & AUTOBIOGRAPHY / People with Disabilities; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; Culture sourde; Deaf culture; Deaf -- United States -- Biography; Mannequins (Personnes) -- États-Unis -- Biographies; Models (Persons) -- United States -- Biography; Personnes sourdes -- États-Unis -- Biographies; Autobiographies; Autobiographies; Autobiographies; Autobiography